PROBLEMATIKA PLURALISME AGAMA ANTARA TEOLOGI DAN FILSAFAT: MEMBACA KRITIK MARIANNE MOYAERT ATAS JOHN HICK - Abdullah Muslich Rizal Maulana (LP2M IAIN Palangka Raya, 2020)
Religious pluralism as an effort to bridge harmony among adherents of religions initiates both theological and philosophical problems. For example, religious pluralism is not only seen as a further effort to build interreligious relationships but also it is built on Truth Relativism. The religious pluralism concept also encourages Marianne Moyaert to investigate religious pluralism more deeply, especially referring to the concept of 'Global Theology' which is conceptualized by John Hick. This paper analyzed a number of theologians' annoyance with Global Theology such as: Hick as a 'Problematic Theologian', demythologizing of Jesus, and most importantly, the blurred relationship between Theology and Philosophy. Following Marianne's Argument, it was believed that the relationship among religions should be built on clear boundaries between Theology and Philosophy, where the boundaries were destroyed by Global Theology. Instead of fading the boundaries between the two, the relationship among religions should be carried out based on a religious understanding based on commitment.